2009
DOI: 10.3349/ymj.2009.50.6.771
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Threshold of Korean Adolescents Associated with the Use of Personal Music Players

Abstract: PurposeHearing loss can lead to a number of disabilities and can reduce quality of life. Noise-induced hearing losses have become more common among adolescents due to increased exposure to personal music players. We, therefore, investigated the use of personal music player among Korean adolescents and the relationship between hearing threshold and usage pattern of portable music players.Materials and MethodsA total of 490 adolescents were interviewed personally regarding their use of portable music players, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
4
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(131 citation statements)
references
References 14 publications
10
98
4
19
Order By: Relevance
“…A longitudinal study by Biassoni et al (2014) also found significant hearing changes and positive large d values at frequencies from 0.25 to 16 kHz by comparing hearing threshold changes over a three year period with music exposure. In addition, similar results were obtained in the studies by Kim et al (2009) and Le Prell et al (2013), showing significantly worse hearing thresholds in participants who used PLDs for 5 years or more than for those who had less experience of using PLD. However, it is noteworthy that only a small effect size was found in the studies of Kim et al (2009) and Le Prell et al (2013), which is mainly due to a different comparison design and the sample size.…”
Section: Near Here)supporting
confidence: 74%
See 1 more Smart Citation
“…A longitudinal study by Biassoni et al (2014) also found significant hearing changes and positive large d values at frequencies from 0.25 to 16 kHz by comparing hearing threshold changes over a three year period with music exposure. In addition, similar results were obtained in the studies by Kim et al (2009) and Le Prell et al (2013), showing significantly worse hearing thresholds in participants who used PLDs for 5 years or more than for those who had less experience of using PLD. However, it is noteworthy that only a small effect size was found in the studies of Kim et al (2009) and Le Prell et al (2013), which is mainly due to a different comparison design and the sample size.…”
Section: Near Here)supporting
confidence: 74%
“…Furthermore, most studies obtained the samples from a single institution, introducing sampling bias, whereas only three studies by Kim et al (2009), Muchnik et al (2012 and Gilliver et al (2012) years, and they were all college students more likely to use PLDs.…”
Section: Sample Size and Qualitymentioning
confidence: 99%
“…Health consequences of using headphones and earphones: documented studies on the consequences of prolonged use of the headphone among adolescents and young adults are rarely found in the literature and a few studies have been conducted on the harmful effects of using headphone and music player (1,2,8,9). In addition, the information about the negative short-term and or long-term complications of using headphone has not been conveyed adequately to the general population.…”
Section: Dear Editormentioning
confidence: 99%
“…This problem might be related to increasing use of music player devices among them (1,2,6). Unfortunately, the adolescents or young people expose themselves to loud noise or music for a long period, while they are unaware of its consequences (4).…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation